Mosaic uniparental disomy results in GM1 gangliosidosis with normal enzyme assay. Issue 1 (21st November 2017) - Myers, Kenneth A.; Bennett, Mark F.; Chow, Chung W.; Carden, Susan M.; Mandelstam, Simone A.; Bahlo, Melanie; Scheffer, Ingrid E.
Abstract : Inherited metabolic disorders are traditionally diagnosed using broad and expensive panels of screening tests, often including invasive skin and muscle biopsy. Proponents of next‐generation genetic sequencing have argued that replacing these screening panels with whole exome sequencing (WES) would save money. Here, we present a complex patient in whom WES allowed diagnosis of GM1 gangliosidosis, caused by homozygous GLB1 mutations, resulting in β‐galactosidase deficiency. A 10‐year‐old girl had progressive neurologic deterioration, macular cherry‐red spot, and cornea verticillata. She had marked clinical improvement with initiation of the ketogenic diet. Comparative genomic hybridization microarray showed mosaic chromosome 3 paternal uniparental disomy (UPD). GM1 gangliosidosis was suspected, however β‐galactosidase assay was normal. Trio WES identified a paternally‐inherited pathogenic splice‐site GLB1 mutation (c.75+2dupT). The girl had GM1 gangliosidosis; however, enzymatic testing in blood was normal, presumably compensated for by non‐UPD cells. Severe neurologic dysfunction occurred due to disruptive effects of UPD brain cells.